A Simple Method to Retract the Descending Palatine Neurovascular Bundle during Osseous Removal of Posterior Interferences in le Fort i Osteotomy - Rodrigues, Moacyr Tadeu Vicente; Mendes, Bruno Coelho [UNESP]; Borba, Alexandre Meireles; Nóia, Claudio Ferreira (My University, 2022)
For accurate repositioning of the maxilla in Le Fort I osteotomy, bone removal around the descending palatine neurovascular bundle and maxillary tuberosity is frequently required. Such task can be challenging due to the high vascularity of the region, which is the most common site of hemorrhage during removal of bony interferences. Although a rare occurrence, ligation of the descending palatine artery in cases of intraoperative vascular damage can be related to the development of aseptic necrosis. This article reports a simple technique for retraction and protection of the descending palatine neurovascular bundle during bony removal related to a posterior maxillary impaction, which can be easily reproduced in orthognathic selected cases.
Keywords: Descending palatine artery; hemorrhage; Le Fort I osteotomy; umbilical tape; vascular injury